ADVERTISING ATTRACTIVENESS, PRICE DISCOUNT, INFLUENCER MARKETING CUSTOMER PURCHASE DECISION MEDIATING BY ONLINE CUSTOMER REVIEWS: A STUDY FROM FASHION H&M DI ZALORA - Purba, John Tampil; Letitia, Shareen (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This study aims to evaluate the influence of advertising attractiveness, price discount, and influencer marketing on purchasing decisions for H&M fashion products on the Zalora platform. The research also pays attention to the role of online customer reviews as a mediator in influencing marketing factors on purchasing decisions. The research method uses a quantitative approach by distributing electronic questionnaires through Google Forms in the JABODETABEK area with respondents aged 13-45 years. The data collected will be analysed using IBM SPSS Statistics version 26 and AMOS version 26. The results showed that advertising attractiveness, price discount, and influencer marketing have a positive influence on purchasing decisions, supported by online customer reviews as a mediator. This research is expected to deepen the understanding of marketing factors that are significant in making purchasing decisions and contribute to future research.